Unified Social Control Through International Law For Mobility During Covid-19 Pandemic - Victor Christian, Axel (Technium Social Sciences Journal, 2022)
States takes measure during Covid-19 Pandemic. Those measures are not unified under the same standard thus limiting mobility. With the vaccine then available the measures and standards states take becomes more complicated and not unified. There needs to be a unified measure which is a unified social control through international law by analysing whether social control is permissible under international law. A unified social control for measures that effect the mobility will unify standards. It is permissible considering the states behaviour under the current Covid-19 Pandemic. Unified control through international should be done in a treaty or convention. Diplomacy for the success of the treaty then should be done through track two model of diplomacy which will provide freedom to the states in raising their wills and concern on the respective treaty.